Cell culture-derived influenza vaccines from Vero cells: a new horizon for vaccine production. (May 2012) - Montomoli, Emanuele; Khadang, Baharak; Piccirella, Simona; Trombetta, Claudia; Mennitto, Elisa; Manini, Ilaria; Stanzani, Valerio; Lapini, Giulia
In the 20th century, three influenza pandemics killed approximately 100 million people. The traditional method of influenza vaccine manufacturing is based on using chicken eggs. However, the necessity of the availability of millions of fertile eggs in the event of a pandemic has led research to focus on the development of cell culture-derived vaccines, which offer shorter lead-in times and greater flexibility of production. So far, the cell substrates being evaluated and in use include Vero, Madin–Darby canine kidney, PER.C6 and insect cells. However, Vero cells are the most widely accepted among others. This review introduces briefly the concepts of advanced cell culture-derived influenza vaccine production and highlights the advantages of these vaccines in terms of efficiency, speed and immunogenicity based on the clinical data obtained from different studies.